2016
DOI: 10.19113/sdufbed.25487
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter Yields and Some Quality Features of Alfalfa (<i>Medicago sativa</i> L.) Cultivars under Two Different Locations of Turkey

Abstract: This research was conducted to determine the dry matter yields and some quality features of alfalfa cultivars in Ankara and Isparta locations of Turkey. In this study, six alfalfa cultivars, (Daisy, Prosementi, Savas, Bilensoy, Gea) which one of them is candidate were tested in the randomized block design with three replications in 2007-2009 growing seasons. According to the results, significant differences were determined in terms of plant height, main stem diameter, stem number, dry matter yield, crude prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Mean DM yields varied significantly (P<0.05) among accessions and ranged from 3.86 t DM/ha for ILRI_14176A to 4.99 t DM/ha for ILRI_7323A. This was to be expected as previous studies have reported significant differences in DM yields among alfalfa cultivars, with yields of 2.0-3.3 t DM/ha (Yüksel et al 2016), and 2.6-3.6 t DM/ha (mean 3.2; Altinok and Karakaya 2002) under rain-fed conditions.…”
Section: Discussionsupporting
confidence: 57%
“…Mean DM yields varied significantly (P<0.05) among accessions and ranged from 3.86 t DM/ha for ILRI_14176A to 4.99 t DM/ha for ILRI_7323A. This was to be expected as previous studies have reported significant differences in DM yields among alfalfa cultivars, with yields of 2.0-3.3 t DM/ha (Yüksel et al 2016), and 2.6-3.6 t DM/ha (mean 3.2; Altinok and Karakaya 2002) under rain-fed conditions.…”
Section: Discussionsupporting
confidence: 57%
“…These differences could be due to cultivar and ecological differences. In the studies conducted with alfalfa varieties and lines under Erzurum ecological conditions (Sengul et al, 2003), as well as with alfalfa varieties in Ankara and Isparta (Yuksel et al, 2016), it was reported that the crude protein contents ranged between 15.95-18.21 % and 15.14-19.13 %, respectively. It could be said that the crude protein contents obtained from our research were within those ranges of change, and they were similar to the results (16.23-17.53 %) of the research conducted by Yilmaz and Albayrak (2016) under Isparta ecological conditions.…”
Section: Crude Protein Contentmentioning
confidence: 99%
“…In 2020, the number of stems significantly decreased so their crops were thinner in the soil with and without mobile Al (Table 2). Other researcher suggested that the stem density of alfalfa depended on resistance of genotypes to acid soil and locations of growing (Lakić et al, 2019; Yüksel et al, 2016). The seed yield of alfalfa depended on environmental conditions because the weather conditions were hot and dry during the formatting and ripening of alfalfa pods in 2019.…”
Section: Discussionmentioning
confidence: 99%